Riset Dakwah Berbasis Media Teknologi Informasi Dan Komunikasi - Safitri, Evis Diah (Universitas Nahdlatul Ulama Blitar, 2023)
This paper is a type of qualitative paper with observation data collection techniques in the form of researcher observations, both through books, journals and online media. This study aims to understand how Information and Communication Technology (ICT) Media-Based Da'wah Research is a challenge and opportunity for a da'i. So that later the results of this study can be a solution to the development of da'wah itself. So that later the results of this study can be a solution to the development of da'wah itself. Along with technological developments, the media has also experienced extraordinary developments. Various social media have sprung up that try to attract the masses as users. This is where the author tries to weigh the extent of social media opportunities that can be filled with da'wah activities and what challenges face preachers in this increasingly sophisticated mass media era. The result is that da'wah through the media is easier to do because people have been integrated with the advancement of social media technology, but the world of da'wah has various challenges that are very risky to the continuity of the values of al-karimah morals which are the focus and core of the da'wah.